Effects of attentional focus cues on lower extremity kinematics during inside of the foot soccer trap among expert soccer players. Issue 4 (August 2021) - LoSarah, Ladule Lako; Jagodinsky, Adam E; Torry, Michael; Smith, Peter J
Numerous studies have demonstrated improved performance results for sport skills through attentional focus instructions. However, few studies have examined the effects of cueing on expert kinematic performance, and this is the first to assess cueing's kinematic effects on expert soccer players performing .common techniques This study assessed the lower extremity kinematics of an inside of the foot soccer trap via motion capture cameras under different attentional focus cues to analyze how the cues affect the movement pattern among expert performers. 10 NCAA Division 1 soccer players trapped a launched ball on a scoring mat after receiving coaching cues inducing an internal, external, holistic, or control focus of attention. Statistical analysis revealed movement differences between the internal and external cue conditions for the ankle and knee joints during the movement. The difference at the knee was a steeper flexion followed by a correction and, at the ankle, a steeper flexion, both during the internal cue condition. Attentional focus cues inducing a conscious control of the movement may disrupt the movement patterns of highly skilled expert performers. Coaches should be acutely aware of the language they use in instruction, even among expert performers.